Financial Literacy and Personal Financial Planning among the Households of Migrant Workers in Rainas Municipality, Lamjung, Nepal - Ghimire, Anup; Danuwar, Ranjana Kumari; Gurung, Bimla Kumari; Dhakal, Ajaya; Timalsina, Dhurba Prasad; Baral, Deep Kumar (Journal of Innovation in Academia, 2023)
Worker’s remittances are one of the most crucial sources of income, contributing significantly to poverty alleviation in households and communities in many parts of the developing world. A pressing concern is whether individuals will be able to maintain their current standard of living upon permanently returning to Nepal. Therefore, the aim of this study is to identify the different factors that affect personal financial planning among migrant households. The study employs an explanatory research design to examine the relationship between various factors that influence the personal financial planning of migrant households. It utilizes a purposive sampling method, collecting data from 100 respondents across 10 wards in Rainas Municipality, along with 10 randomly selected respondents. Data is collected through Google Forms and analyzed using SPSS (version 21), SPSS AMOS, and MS-Excel. The results reveal that the majority of households earn around 45,000 to 60,000 per month, indicating a healthy income inflow. The structural equation modeling (SEM) analysis shows that financial awareness (β= 0.218, P<0.05) has a significant relationship with financial planning, while financial knowledge (β= -0.085, P>0.05) and financial attitude (β= 0.044, P<0.05) do not have a significant relationship with financial planning. This study suggests that financial awareness is a key factor in increasing financial knowledge and improving financial attitudes, ultimately enhancing financial planning in households. To promote such awareness, the government can consider incorporating financial courses into school curricula to enhance financial literacy and personal financial planning.